5(x-5)+9=3(x-4)

Simple and best practice solution for 5(x-5)+9=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-5)+9=3(x-4) equation:


Simplifying
5(x + -5) + 9 = 3(x + -4)

Reorder the terms:
5(-5 + x) + 9 = 3(x + -4)
(-5 * 5 + x * 5) + 9 = 3(x + -4)
(-25 + 5x) + 9 = 3(x + -4)

Reorder the terms:
-25 + 9 + 5x = 3(x + -4)

Combine like terms: -25 + 9 = -16
-16 + 5x = 3(x + -4)

Reorder the terms:
-16 + 5x = 3(-4 + x)
-16 + 5x = (-4 * 3 + x * 3)
-16 + 5x = (-12 + 3x)

Solving
-16 + 5x = -12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-16 + 5x + -3x = -12 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-16 + 2x = -12 + 3x + -3x

Combine like terms: 3x + -3x = 0
-16 + 2x = -12 + 0
-16 + 2x = -12

Add '16' to each side of the equation.
-16 + 16 + 2x = -12 + 16

Combine like terms: -16 + 16 = 0
0 + 2x = -12 + 16
2x = -12 + 16

Combine like terms: -12 + 16 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 9+0.50x=0 | | (7a+1)(6a^2+8a+6)= | | 16+2x=0 | | y=16+2x | | 2-4x-x^2=0 | | x^2-0x-1=0 | | x(2-x)(2+x)-(-X-2)=0 | | -6y^2-9x+1=0 | | -3x+6=-2(3x+6) | | -3(5y-7)+2(4y+6)= | | 6(2x-4)=36 | | 5x-(3x-4)=17 | | 4x^2-28x+11=0 | | 6(13-2x)=50-x+46 | | 0+11y=7 | | 0+11y=y | | 2(4x+3)=12x+4-4x+2 | | 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 |

Equations solver categories